Effects of Combing Group Executive Functioning and Online Parent Training on School-Aged Children With ADHD: A Randomized Controlled Trial - Chu, Liting; Zhu, Peiying; Ma, Chenhuan; Pan, Lizhu; Shen, Li; Wu, Danmai; Wang, Yu; Yu, Guangjun (Frontiers in Pediatrics, 2022)
Abstract Objective: The acceptance of drug treatment for younger children with Attention-deficit/hyperactivity disorder (ADHD) in China remains low. Here we explored the clinical benefits of a non-pharmaceutical intervention method combining group executive function training and online parent training program, termed GEF-OPT, for school-aged students with ADHD through a randomized controlled trial. Method: A total of 145 children (aged 6-8 years) were formally registered and randomized to the intervention group (n=73) and waitlist group (n=72). The enrolled children received 8 sessions of GEF-OPT treatment which consists of a hospital-based children EF training program and an online parent training program. Treatment outcome was assessed by parent/teacher report questionnaire and neurophysiological experiment. Results: After 8 sessions of intervention, children in the intervention group showed significant improvement in inattentive symptom compared to the waitlist group (14.70±4.35 vs. 16.03±2.93; p = 0.024), but insignificant difference in hyperactive-impulsivity (9.85±5.30 vs. 10.69±5.10; p = 0.913). Comorbid oppositional defiant disorder was significantly reduced in the intervention group (7.03±4.39 vs. 8.53±4.41; p = 0.035). Children in the intervention group had greater reduction in scores of behavioral regulation index (inhibition, emotional control) and metacognition index (working memory, planning/organization, monitoring) in executive function than those in the waitlist group (p < 0.05). Significant effects were also found in learning problem of WEISS Functional Impairment Scale-Parent form and parental distress between two groups at post-treatment (p < 0.05). In line with this, the result of Go/No-Go task showed significant improvements in accuracy change (4.45±5.50 % vs. 1.76±3.35 %; p = 0.001) and reaction time change (47.45±62.25 s vs. 16.19±72.22 s; p = 0.007) in the intervention group compared with the waitlist group. Conclusion: We conclude that participants in GEF-OPT program improved outcomes for inattentive symptom, executive function, learning problems and parental distress. GEF-OPT is a promising non-pharmaceutical therapeutic option for younger children. Trial Registration: ChiCTR2100052803